Peranan Kelompok Tani dalam Usahatani Kakao di Desa Lambandia Kecamatan Lambandia Kabupaten Kolaka Timur - Parawansa, Dian; Arimbawa, Putu; Salahuddin, Salahuddin (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study aims to determine the role of farmer groups in cocoa farming in the Lambandia village,Lambandia District. This research was conducted in September 2016. The method used in this research is method of qualitative description analysis, which this method will describe the role of farmer groups in the cocoa farming by using a measuring instrument class interval. Technic of collecting data, taken from the two data sources, are primary data and secondary data. Research variables are the identity of respondents, the role of farmer groups in classroom learning, as a production unit, and as a forum for cooperation, as well as cocoa farming activities which include maintenance, harvesting, post-harvest and marketing. The results showed that, the role of farmer groups in cocoa farming activities in the Lambandia village, Lambandia District has enoughlarge role in the classroom learning and production units, nevertheless the farmer group has a lesser role as a co-operative unit in cocoa farming activities.